Gastric Siderosis Due to Oral Ferrous Sulfate Supplements. Issue 10 (12th October 2022) - Tun, Kyaw Min; Naga, Yassin; Mesgun, Sami; Aponte-Pieras, Jose; Jinadasa, Priyanthi; Ohning, Gordon
ABSTRACT: Gastric siderosis is the deposition of excess amount of iron from oral ferrous sulfate supplements to the gastric mucosa. It is an often overlooked entity in the literature and can be related to symptoms such as dyspepsia, nausea, and melena through mucosal injury. Different etiologies of gastric siderosis display distinct histopathological patterns. Pattern B, which is most commonly associated with oral iron supplements, is seen when iron is deposited in the extracellular space of the lamina propria. It is crucial to consider gastric siderosis as a potential diagnosis in symptomatic patients and to evaluate the necessity of oral ferrous sulfate supplements.